2016
DOI: 10.5194/bg-13-3619-2016
|View full text |Cite
|
Sign up to set email alerts
|

No-tillage lessens soil CO<sub>2</sub> emissions the most under arid and sandy soil conditions: results from a meta-analysis

Abstract: Abstract. The management of agroecosystems plays a crucial role in the global carbon cycle with soil tillage leading to known organic carbon redistributions within soils and changes in soil CO 2 emissions. Yet, discrepancies exist on the impact of tillage on soil CO 2 emissions and on the main soil and environmental controls. A meta-analysis was conducted using 46 peer-reviewed publications totaling 174 paired observations comparing CO 2 emissions over entire seasons or years from tilled and untilled soils acr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
73
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(83 citation statements)
references
References 108 publications
6
73
2
2
Order By: Relevance
“…Conservation tillage merely reduces soil disturbance and normally does not add extra materials to soils. For example, NT increased SOC by 7% in the 0-3 cm soil layer (Abdalla et al, 2016) and by 3% at the 40 cm depth . Biochar is a carbon-rich material with a charged surface, organic functional groups, and a porous structure, which can potentially increase soil aggregation and cation exchange capacity (Jien & Wang, 2013).…”
Section: Soil Propertiesmentioning
confidence: 96%
See 2 more Smart Citations
“…Conservation tillage merely reduces soil disturbance and normally does not add extra materials to soils. For example, NT increased SOC by 7% in the 0-3 cm soil layer (Abdalla et al, 2016) and by 3% at the 40 cm depth . Biochar is a carbon-rich material with a charged surface, organic functional groups, and a porous structure, which can potentially increase soil aggregation and cation exchange capacity (Jien & Wang, 2013).…”
Section: Soil Propertiesmentioning
confidence: 96%
“…Although these CSA management practices have been widely used to enhance soil health (e.g., Denef, Zotarelli, Boddey, & Six, 2007;Fungo et al, 2017;Thomsen & Christensen, 2004;Weng et al, 2017), their effects on SOC sequestration are variable and highly dependent on experiment designs and site-specific conditions such as climate and soil properties (Abdalla, Chivenge, Ciais, & Chaplot, 2016;Liu et al, 2016;Paustian et al, 2016;Poeplau & Don, 2015). The potential to sequester soil carbon varies greatly among CSA practices, which has not been well addressed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike N 2 O, CA, RT, and NT reduced CO 2 emissions from the soil compared with CT (Abdalla et al, 2013(Abdalla et al, , 2016Chatskikh et al, 2008;Jia et al, 2016). Abdalla et al (2016) using a meta-analysis study reported that NT treatments had 21% less CO 2 emissions compared with CT treatments. Jia et al (2016) found that CO 2 emissions were higher by about 7.8% under CT treatment using moldboard plow than under NT.…”
Section: Impact Of Ca On Soil Ghg Emissionsmentioning
confidence: 99%
“…Extensive research on soil GHG has hitherto focused on tillage practice and fertilization (Abdalla, Chivenge, Ciais, & Chaplot, 2016;Bauer, Frederick, Novak, & Hunt, 2006;Jia et al, 2016;Six et al, 2004;Ussiri & Lal, 2009), but GHG emissions involves a complex interaction of many factors. According to Bilandžija, Zgorelec, and Kisić (2016), focusing on one or two factors may lead to different results across studies.…”
Section: Impact Of Ca On Soil Ghg Emissionsmentioning
confidence: 99%